Effects of replacing antimicrobials with medium chain fatty acids on nursery pig growth - Luebcke, Grace Ellen; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
An increase in regulations and consumer pressure limiting the use of feed-grade antimicrobials in swine diets and negative environmental impacts associated with using ZnO for growth purposes has caused pressure to find replacements. There is little data to show the efficacy of medium chain fatty acid (MCFA) in nursery pig diets. This study was conducted to evaluate MCFA as a potential replacement for antimicrobials. 360 weanling pigs were divided into a completely randomized experiment with 6 treatment groups: 1) negative control, 2) 3000 ppm ZnO in phase 1 and 1500 ppm in phase 2, 3) 50 g/ton carbadox, 4) 1% C6:C8:C10 blend, 5) 1% Feed Energy R2 (Feed Energy Corp., Des Moines, IA), 6) 1% FORMI GL (ADDCON, Bitterfeld-Wolfen, Germany). There were 6 pigs/pen, with pen as EU, and 10 replicates/treatment. In a 35 d trial, treatment diets were fed in 2 phases from d 0 to 19 with a common phase 3 diet from d 20 to 35. Pigs and feeders were weighed weekly to calculate ADFI, G:F, and ADG. From d 0 to 19, ADG was greater for (P<0.05) for pigs fed ZnO and carbadox than pens on control or R2, while those fed C6:C8:C10 blend or FORMI were similar (P>0.05) to carbadox. Differences in G:F were marginally significant (P=0.078). Day 19 body weight was greater (P<0.05) in pigs fed ZnO versus control. During the common period, there was no significant impact on G:F (P=0.320). These data suggest that ZnO and carbadox continue to improve nursery performance. Products such as FORMI GML show results similar to carbadox, while others display variable performance. Further research is warranted to evaluate the efficacy and inclusion rate of MCFA products to replace feed-grade antimicrobials.
Keywords: Spring 2019